Sex-specific familial clustering of myocardial infarction in patients with acute coronary syndromes. (22nd September 2015) - Banerjee, A; Silver, LE; Heneghan, C; Welch, SJV; Bull, LM; Mehta, Z; Banning, AP; Rothwell, PM
Abstract : Background: A family history of premature myocardial infarction (MI) in first degree relatives is a risk factor for MI, and an indication for primary prevention. Although excess mother-to-daughter "transmission" occurs in ischaemic stroke, no published studies have considered sex-of-parent/sex-of-proband interactions in the heritability of MI. Methods: In a population-based study (Oxford Vascular Study) of all patients with acute coronary syndromes (ACS), irrespective of age, a family history of all acute vascular events and related risk factors was analysed by sex and age of both probands and first-degree relatives. Premature events were categorised as occurring at age uner 65 years. Results: Of 835 probands with one or more ACS, 623 (420 males) had incident events and complete family history data. In probands with premature ACS, a maternal history of both MI and of all vascular events was more common in female than male probands (OR 2.25, 1.02 to 4.94, p = 0.04 and 3.03, 1.47 to 6.26, p = 0.002 respectively). No such effect existed for paternal history (OR 1.00, 0.46 to 2.10, p = 0.99 and 1.19, 0.58 to 2.43, p = 0.63, respectively). Age at ACS in probands was highly correlated with age at MI in mothers (r  =  0.46, p<0.001) regardless of the proband's sex. Consequently, a history of premature maternal MI was strongly associated with premature ACS and premature MI in female (OR 10.52, 2.17 to 56.6, p = 0.001 and OR 7.31, 1.55 to 34.6, p = 0.004, respectively) and male (3.88, 1.20 to 12.6, p = 0.01 and OR 3.63, 1.13 to 11.60, p = 0.02, respectively) probands (see table). Conclusions: Family history is a risk factor for coronary heart disease that is easily available to clinicians. However, family history data are currently underutilised in risk scores. Even risk prediction tools designed for low-resource settings, in which other technology-dependent risk factors are not available, have usually excluded family history. Important sex-of-parent/sex-of-proband interactions exist in the family history of MI in patients with ACS. Greater emphasis should be placed on maternal than paternal history of MI, particularly in women aged under 65 years. Although young women have a low incidence of MI, case-fatality is more than double that for young men and young women with a family history of MI demonstrate less coronary heart disease risk awareness and worse lifestyle choices than men.